Design de transformadores cerâmicos piezoelétricos e aplicações - Gaiotto, Fernando José (2012)
This work is to study models (design) of radial mode piezoelectric transformers are constructed with ferroelectric ceramic Pb(Zr,Ti)O3 for applications in power conversion. We explore how to apply their physical characteristics and use them as a component for building a reactor to a fluorescent lamp. We applied an electrical equivalent circuit model of a piezoelectric transformer with applications in power conversion using switched high resonant frequency (25kHz - 2MHz). The piezoelectric transformer is a device that combines a piezoelectric actuator (primary side) with a piezoelectric transducer (secondary side), where both can work with vibration modes of transverse or longitudinal. These actuators and transducers are made of piezoelectric elements, which in turn made up of plates (electrodes) and polarized ferroelectric ceramics. This work also explored the models of multilayer building a TP over a piezoelectric element as actuator for greater load power and high voltage gain. The modeling power, considering its operation and analyzes the characteristics of a piezoelectric transformer model were performed by measurements and simulations that allowed the best choice for use in a prototype of the lamp ballast. The use of ceramic transformer is justified because of the simplicity of large-scale production at low cost.